Pelanggaran Prinsip Kesopanan dalam Stand Up Comedy Bertajuk Somasi: Violation of the Principle of Decency in Stand-Up Comedy Titled Somasi - Sari, Ajeng Maulia; Kinanti, Kingkin Puput; Susandi, Susandi (Information Technology and Science(ITScience), 2025)
The principle of politeness is one of the fields of study in pragmatics; Geoffrey N. Leech (1983) stated that pragmatics is the study of meaning in the context of various speech situations. Applying the principle of politeness is necessary in communication so that it can run well and correctly. However, sometimes, many people still do not comply with the principle of politeness for some interests, for example, in humor discourse, namely stand-up comedy. In stand-up comedy, violating the principle of politeness is something that comedians must do; this is done to present a funny impression to make the audience laugh. Considering comedians often commit many violations, researchers are interested in researching